Bimbingan Kelompok Dalam Meningkatkan Kepercayaan Diri Siswa Dalam Penyesuaian Diri Siswa Kelas VII di SMP Negeri 2 Sragi Lampung Selatan - Yanti, Noffi; Martin, Jon; Almubasyir, Khuzaifah (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2023)
Students have problems related to their level of self-confidence and ability to adapt. Group guidance is an effort to help new students increase their new self-confidence in adapting. Therefore, SMP N egeri 2 South Lampung is making efforts to help new students through group guidance. The aim of this research is to reveal the guidance group in increasing students' self-confidence in adjusting to class VII students at SMP Negeri 2 Lampung. This type of research is field research (field research) which is descriptive qualitative in nature. The data sources in this research were 9 people, consisting of 7 class VII students, 1 guidance counselor and 1 homeroom teacher. The data collection techniques used were interviews, observation and documentation. The data analysis technique used is the Miles and Huberman data analysis model, which consists of data reduction, data presentation and conclusions. The results of this research show that the implementation of group guidance in increasing students' self-confidence in adjusting to class VII students has been implemented through four stages, namely: Formation stage, namely the formation of a group of 7 people, introduction of group members, as well as explanation of the aims and objectives of the activity. The transition stage, namely the stage filled with ice-making activities in the form of guessing to lighten the atmosphere. The activity stage, namely the core stage of group guidance here uses group discussion techniques with lecture and question and answer methods. The closing stage, namely the closing of activities which includes evaluation activities, closing messages and expectations, and follow-up (follow-up). The conclusion of this research is that the implementation of guidance groups to increase students' self-confidence in adjusting to class VII students has been successful and has had a positive effect